2021
DOI: 10.1002/jssc.202100768
|View full text |Cite
|
Sign up to set email alerts
|

A novel liquid chromatography‐fluorescence method for the determination of delafloxacin in human plasma

Abstract: Delafloxacin is a novel fluoroquinolone antibiotic that was approved by the European Medicine Agency to treat bacterial infections of the skin and underlying tissues, and community‐acquired pneumonia. Despite being in the market since 2019 in the European Union, there is no published liquid chromatography‐fluorescence method for delafloxacin quantification in biological samples. A novel, rapid, and sensitive high‐performance liquid chromatographic method was developed to determine delafloxacin in human plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Using the ratio C max /MIC (C max : maximal concentration) enables the assessment of the risk of resistance emergence to FQs [ 15 ]. To note, several chromatography methods are already available to monitor DLX plasmatic concentrations [ 34 , 35 ]. The studies of pharmacokinetics and pharmacodynamics (PK/PD) parameters of DLX have shown that the total exposure following a single 300 mg intravenous (IV) dose and a single 450 mg oral (PO, per os) dose is equivalent, allowing change in administration ways.…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%
“…Using the ratio C max /MIC (C max : maximal concentration) enables the assessment of the risk of resistance emergence to FQs [ 15 ]. To note, several chromatography methods are already available to monitor DLX plasmatic concentrations [ 34 , 35 ]. The studies of pharmacokinetics and pharmacodynamics (PK/PD) parameters of DLX have shown that the total exposure following a single 300 mg intravenous (IV) dose and a single 450 mg oral (PO, per os) dose is equivalent, allowing change in administration ways.…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%
“…6.1.5. Potential Role of TDM Liquid chromatography methods have been developed for PK analyses of delafloxacin [188,189,192]. However, no TDM studies have been published and no PK/PD safety/efficacy thresholds have been identified yet.…”
Section: Pk/pd Characteristicsmentioning
confidence: 99%
“…4 This is later associated by Cempra. 5 Veronica Hernandis et al, 6 measured plasma delafloxacin strengths by RP chromatography. Wavelength is 405m and 450nm.…”
Section: Introductionmentioning
confidence: 99%